OPTIMIZING HEALTH SERVICE MANAGEMENT IN UMRAH TOUR OPERATORS: A RETROSPECTIVE ANALYSIS - Yaltafit Abror Jeem; Muhammad Kharisma; Yayuk Fathonah; Arif Budi Santoso; Wahyu Agung Sudrajat (Institut Agama Islam Negeri Metro, 2026)
Private Umrah tour operators (PPIU) rarely utilize morbidity data for health service management. This retrospective descriptive study analyzes 783 medical consultations from a PPIU between October 2024 and February 2025 to optimize health logistics and operational strategies. The analysis reveals that morbidity is dominated by acute respiratory infections (38.4%) and musculoskeletal disorders (28.1%), followed by hypertension/cardiovascular issues (10.2%), gastrointestinal disorders (8.5%), and dermatitis (5.8%). A distinct seasonal peak occurred during the winter months (December–January). Furthermore, elderly pilgrims (>60 years) demonstrated a significantly higher risk of fatigue-induced hypertension. These findings emphasize that Umrah health needs are highly predictable. The study concludes that PPIUs must shift from reactive care to proactive, data-driven health logistics. This involves integrating internal morbidity surveillance into pharmaceutical forecasting, adjusting medical supplies seasonally, and implementing targeted preventive programs for high-risk groups. Training tour leaders to manage pilgrim fatigue is identified as a critical operational strategy to enhance logistical efficiency, pilgrim safety, and service competitiveness.